The high pressure catalytic hydrogenation of the tannin of black wattle (Acacia mollissima Willd) - Silk, M H (Rhodes University, Faculty of Science, Department of Chemistry, 1947)
From Introduction: The wattle industry in South Africa has, from its commencement in the middle of the last century, gradually assumed a position of increasing importance in the economic structure of the country. Apart from the provision of a valuable tanning extract for home use and for export, the tree itself has proved of considerable importance to the Union's mining industries. In addition there would appear to be possibilities for the utilisation in the near future, of the raw ground bark and the wattle extract for the manufacture of a number of by-products, including certain types of plastics.
Keywords: Uncatalogued